Sanitizing, caring and civilizing: the medical discourse for schools in the state of Paraná (1920-1937) - Liliana Müller Larocca; Vera Regina Beltrão Marques (Faculdade de Medicina de Botucatu (Unesp), 2010)
Based on the investigation of medical discourses referring to school sanitation, this study addresses the spread of the Hygiene science in the State of Paraná, southern Brazil, between 1920 and 1937. Discourses to schools present in many sources, mainly periodicals, Archivos Paranaenses de Medicina and Revista Medica do Parana, pointed out the perception of medicine underpinned by Hygiene, in which doctors advocated a new social function: educators. By discussing intervention in schools and their users, doctors intended to "care for, protect and sanitize infancy", a task aiming to insert the territory of Paraná in the national process of hygienic and social sanitation. It is a historical research study, inspired by Norbert Elias' ideas of Civilizing Process. Thus, its purpose is to recognize civility proposals in the medical discourses created to the schools of the State of Paraná. Educational conceptions in the studied period evolved from knowledge, prescriptions and discourses on Hygiene science and its greatest advocates - the doctors.